(untitled) (Acta Polytechnica CTU Proceedings, 2024)
In this paper, woven glass fiber composite samples were subjected to three different cyclic loading histories (i.e., tensile, shear and combined loading at 45° via the Modified Arcan Fixture. During the experiments, the samples were monitored by a stereovision system. Finite Element based stereocorrelation was used to measure the displacement and strain fields. The analysis of the experiments revealed different damage mechanisms. Furthermore, for the 45° experiment, the highest strain levels were reached, whereas for the tensile test, the highest stress levels were achieved.